Pengaruh Customer Experience, Discount, dan Strategy Location terhadap Loyalitas Pelanggan pada PT. Lion Parcel Pos Rawe Tangkahan - Delara Sidebang; Yuli Arnida Pohan (Pusat Riset dan Inovasi Nasional, 2024)
This research aims: to find out whether there is an influence of customer experience discounts, location strategy on customer loyalty at PT. Lion Parcel Rawe Tangkahan branch, The method used in this research is a quantitative method, the number of samples in the research was 100 respondents. The blood collection technique in this research is a questionnaire and questionnaire given to customers at PT. Lion Parcel Rawe Tangkahan branch. Data processing in research uses SPSS23 for windows. Based on the results of this research, it shows that customer experience has a partial and significant effect on customer loyalty as seen from the t-count value of 7.454 > 1.984 with a sig value < 0.05. Discounts have a partial and significant effect on customer loyalty as seen from the t-count value of 2.006>1.985 with a sig value <0.05. Location strategy has a positive and significant effect on customer loyalty as seen from the t-count value of 2.381> 1.985 with a sig value <0.05. Customer experience, discounts, and location strategy simultaneously and significantly influence customer loyalty with an f-value of 83.421> 2.699 f-table value, with a value of 0.00 < 0.005.